Thermal Efficiency And Heat Removal Factor For Hybrid Photovoltaic Thermal PVT System - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Sachit, Fadhil Abdulameer (Penerbit Akademia Baru, 2019)
Heat removal factor (FR) is vital in determining the photovoltaic thermal (PVT) system thermal efficiency. (FR) represents the ratio of the actual (useful) heat gain via the heat transfer fluid that flows through a collector to the entire collector surface. In this study, simulations were conducted on three configurations using the PVT new design (dual oscillating absorber) to determine (FR) and thermal efficiency. Using different tube gaps and tube diameters D, the designs were compared using validated model, which was presented using the MATLAB programme theoretical data. The findings indicate that the shape, gap, and diameter of the absorber tubes are crucial to the PVT performance. The study was done under solar radiation level of 300-1000 W/m2 and mass flow rate of 0.01 kg/s at each solar radiation level. The results show that the best thermal efficiency of the new PVT designs reached ηth 31, 58%, and The heat removal factor can reach (FR) 0.47 for dimension tube diameters 0.015m and tube gap 0.03m The continuous operation of the flowing water through absorber result reduces the temperature of the PV cells and simultaneously increasing it efficiency.